Update of Key Clinical, Histological and Molecular Features of Malignant Bone Tumours Arising in the Craniofacial Skeleton - Haefliger, Simon; Andrei, Vanghelita; Baumhoer, Daniel (Frontiers in Oncology, 2022)
The craniofacial skeleton is a highly complex and specialized anatomic region containing and protecting the brain and sensory organs. Bone sarcomas arising here comprise a heterogeneous group of tumours, some of which differ in their biological behaviour compared to their peripheral counterparts. The reasons for this seem to lie, at least partially, in the embryonal development of the craniofacial bones. For reaching the correct diagnosis as the cornerstone of optimal personalised treatment planning, a multidisciplinary team of specialists, including pathologists, radiologists, oncologists, and head and neck surgeons needs to be involved. The most common tumours arising in the craniofacial bones are bone-forming tumours, cartilage-forming tumours, fibro-osseous lesions, giant cell-rich lesions, and notochordal tumours. While morphology remains the backbone for the diagnosis, the last decade has witnessed tremendous advances in the molecular characterization of tumours, and molecular testing is increasingly becoming a part of the diagnostic process. The integration of these new molecular markers into the diagnostic approach has undoubtedly increased the diagnostic accuracy and objectivity, and holds great promise to also identify new therapeutic targets for precision medicine in the future. Examples include HEY1-NCOA2 in mesenchymal chondrosarcoma, IDH1/2 mutations in chondrosarcoma and TFCP2 rearrangements in rhabdomyosarcoma. In this article, key clinical, histological and molecular features of malignant bone tumours arising in the craniofacial region are discussed, with a special focus on the differential diagnosis and prognostic considerations.